Development of Observation Instruments for Partnership Model-Based Learning Activities in Distance Learning in Elementary Schools - Arif Widodo; Prayogi Dwina Angga; Muhammad Syazali; Umar Umar (Departement of Mathematics Education, 2023)
Development of Observation Instruments for Partnership Model-Based Learning Activities in Distance Learning in Elementary Schools. The purpose of this study was to determine the feasibility of the partnership model-based observation of student learning activities to measure student involvement in distance learning in elementary schools. This research uses a development research design. Collecting data using a questionnaire, observation, and interviews. Data analysis using descriptive statistics. The results of the study found that the developed instrument received a rating of 4.60 from the expert validator and 4.64 from the user. The findings from this study are that the partnership model-based activity observation instrument that was developed is feasible to use to measure student engagement in distance learning in elementary schools.